THE IMPLEMENTATION OF THEME-BASED TEACHING TO IMPROVE STUDENTS’ SPEAKING SKILL - Fitria Lathufirdaush (Journal of English and Education, 2014)
This article is based on the study conducted in July and August 2013 to identify the improvement of young learners’ speaking skill based on the implementation of Theme-Based Teaching. The study was conducted by using classroom action research design which involved 32 second graders of an Elementary School in Bandung. Furthermore, the data were gathered through speaking assessments and interview. The findings revealed that there was improvement in the students’ speaking skill which covered some aspects, including vocabulary, pronunciation and grammar. This article concludes by reviewing the result of the research and some activities that can be used in improving students’ speaking skill. Keywords: young learners, Elementary School, speaking skill, Theme-Based Teaching